A Randomized Controlled Trial to Investigate the Efficacy of Bioactive Materials in Orthodontic Brackets for Reducing Decalcification - Hafiz Muhammad , Abdul Aleem , Affan Ahmad, Yosra Saeed, Samia Siraj , Rana Modassir Shamsher khan, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Enamel decalcification, manifesting as white spot lesions, remains a prevalent complication duringfixed orthodontic treatment. This randomized controlled trial aimed to evaluate the efficacy oforthodontic adhesives incorporating bioactive materials